2014
DOI: 10.1093/occmed/kqu056
|View full text |Cite
|
Sign up to set email alerts
|

The interactions between pain, pain-related fear of movement and productivity

Abstract: Despite the fact that musculoskeletal pain increases the risk of reduced work ability significantly, musculoskeletal pain and pain-related fear of movement were associated with low productivity only among employees with good work ability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 23 publications
1
7
0
1
Order By: Relevance
“…In addition to showing an association between pain intensity and work limitations, this study also showed that high physical work demands aggravate the association of LBP-intensity with work limitations due to pain. This is in accordance with previous studies reporting lower work ability among workers with MSD and high physical work demands [51][52][53][54], while high physical work Table 2 Odds ratios (OR) and 95% confidence intervals (95% CI) for physical work demands and work limitations due to pain stratified by low-back pain intensity among senior workers. The reference group is "Mostly seated work that is not physically demanding" demands also seem to increase sickness absence among workers with MSD [28,[55][56][57][58][59][60][61].…”
Section: Heavy Physical Work and Work Limitiations Due To Lowback Painsupporting
confidence: 91%
“…In addition to showing an association between pain intensity and work limitations, this study also showed that high physical work demands aggravate the association of LBP-intensity with work limitations due to pain. This is in accordance with previous studies reporting lower work ability among workers with MSD and high physical work demands [51][52][53][54], while high physical work Table 2 Odds ratios (OR) and 95% confidence intervals (95% CI) for physical work demands and work limitations due to pain stratified by low-back pain intensity among senior workers. The reference group is "Mostly seated work that is not physically demanding" demands also seem to increase sickness absence among workers with MSD [28,[55][56][57][58][59][60][61].…”
Section: Heavy Physical Work and Work Limitiations Due To Lowback Painsupporting
confidence: 91%
“…The authors suggest that the WAI level ≤ 37 is a clear predictor of the employee's rehabilitation needs. Interesting conclusions have also been provided by a study conducted on Danish production workers, where the correlation between the WAI level and functional pain in the musculoskeletal system was investigated [17]. It was observed that experiencing pain reduces productivity, but it does so to a greater extent in the group of people with a good WAI, rather than in the case of people with moderate work ability.…”
Section: Discussionmentioning
confidence: 98%
“…Despite the obvious improvement in dizziness and the direct concomitant effects on physical and mental well-being, the WAI may not have shown significant changes because it relates to workers with work restrictions. In a literature review article 14 , the authors reported that health is undoubtedly the factor that most interferes with the ability to work and that cardiorespiratory fitness and musculoskeletal functioning are the aspects that have the greatest impact on functional capacity because they are directly related to the performance of work demands 14,26,27 .…”
Section: Discussionmentioning
confidence: 99%